Impacts of primary tumor location on outcomes in patients undergoing hepatectomy for colorectal liver metastasis vary according to tumor burden - Wang, Hong-Wei; Wang, Li-Jun; Li, Juan; Wang, Kun; Xing, Bao-Cai (Frontiers in Surgery, 2022)
ABSTRACT Purpose. The purpose of this study was to verify whether the prognostic value of primary tumor location (PTL) for patients undergoing resection for colorectal liver metastasis (CRLM) is affected by tumor burden. Methods. Patients who underwent a first curative-intent surgery for CRLM from 2006 to 2017 were enrolled. The imaging tumor burden score (TBS) was calculated as TBS2 = (maximum tumor diameter in cm)2 + (number of lesions)2. Then, the prognostic role of PTL was assessed in different TBS zones. Results. The patient population consisted of 524 left-sided (LS) and 118 right-sided (RS) primary tumors. The distribution of TBS in the patient cohort was: Zone1:TBS <3 [n=161 (25.1%)], zone 2: TBS≥3 to <7 [n = 343 (53.4%)], and zone 3: TBS ≥7 [n = 138 (21.5%)]. In the whole cohort, the 5-year overall survival (OS) in the RS group was worse than that in the LS group (35.6% vs. 45.4%). However, after adjustment for known prognostic confounders, the RS group was not independently associated with a poorer OS (HR 1.18, p=0.247). Among patients with TBS <7, OS in the RS group was significantly shorter than that in the LS group in both univariate and multivariate analyses. The prognostic role of PTL remained significant after propensity score matching or excluding patients who received anti-EGFR agents. Conversely, the association between PTL and OS was no longer evident in patients with TBS ≥7. Conclusions. The current study demonstrates that the prognostic value of PTL varies by TBS, and RS tumors are only associated with shorter survival in patients with low or medium TBS.